Asuhan Keperawatan Jiwa pada Tn. S dengan Masalah Utama Resiko Perilaku Kekerasan Akibat Skizofrenia Tak Terinci Diruang Gatotkaca RSJD Dr. Amino Gondohutomo Provinsi Jawa Tengah - Naely Nur Ilahi; Slamet Wijaya; Esti Nur Janah; Titi Sri Suyanti (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Health is an optimal body condition in terms of physical, mental and well-being aspects of life, where individuals are able to live a productive life both individually, socially and economically (Oktavilantika et al., 2023). Mental health according to WHO does not only indicate the absence of mental disorders in the form of changes in thoughts, feelings and behavior that cause inability to carry out activities, but also the presence of positive character that shows the normality of a person's soul so that he is able to carry out his daily life productively. Schizophrenia itself is a serious mental disorder that causes decline or even inability to communicate, cognitive impairment, and difficulty in carrying out daily activities. (Risal et al., 2022 & Afeanpah et al., 2022 ).